Intrameniscal Gouty Tophi in the Knee: A Case Report. Issue 3 (July 2015) - Aoki, Tetsuhiro; Tensho, Keiji; Shimodaira, Hiroki; Akaoka, Yusuke; Takanashi, Seiji; Shimojo, Hisashi; Saito, Naoto; Kato, Hiroyuki
Abstract : Case: We report a case of recurrent acute arthritis and restricted range of motion in the knee joint, with magnetic resonance imaging subsequently detecting a nodular lesion within the lateral meniscus. Knee arthroscopy and histology revealed that the lesion was intrameniscal gouty tophi. After arthroscopic synovectomy and excision of the tophi, the symptoms resolved and the patient remained symptom-free at two years of follow-up. Conclusion: Surgeons should be aware of the presence of such pathology and consider arthroscopic surgery if the mechanical symptoms persist.